Platelet Dysfunction in Migraine: Effect of Self-Medication with Aspirin - Deshmukh, Sunanda V.; Meyer, John Stirling; Mouche, Richard J. (Thrombosis and Haemostasis, 1976)
Circulating microembolic index (CMI) was determined by drawing one blood sample into EDTA-formalin and the other into DTA alone in patients with migraine and compared with matched normal controls. Platelet aggregates, if any, are fixed in EDTA-formalin but dis- aggregated by EDTA. Ratios of these two counts approximate “unity” in normals and are proportionately less than unity, depending on the number of platelet aggregates. 26 untreated migraineurs and 19 migraineurs with history of self-medication with aspirin taken within 72 hours of the test, were studied in headache-free intervals. Results were compared with those from 20 healthy, age and sex matched volunteers, without migraine, who were medication- free for at least one week. Mean CMI in untreated migraineurs (0.77±0.03 SEM) was significantly lower than the mean in normal controls (0.94±0.02, p. <0.002). Migraineurs with selfadministration of aspirin had mean CMI of 0.88±0.02, differing significantly from untreated migraineurs (p <0.01) but not from normal controls (0.1<p<0.2). Results suggest excessive platelet aggregation in migraineurs which tends to be corrected by treatment with platelet inhibitors such as aspirin.